ON VIASMAN-GRAY MANIFOLD WITH GENERALIZED CONHARMONIC CURVATURE TENSOR - Ali A. Shihab; Abdulhadi Ahmed Abd (Tikrit Journal of Pure Science)
The current study deals with  generalized conhormonic ensor of Vaisman - Gray manifold. The aim of this paper to calculate  components  generalized Ricci tensor and generalized Riemannian tensor of -  adjoint -s  to find Generalized conharmonic Curvature tensor of -manifold, one of the an manifold struc es is donated   , w re  a d  re ely de o the near hler m old an ally conformal kahler m fold have been studied